Teaching Middle School Students with Disabilities to Solve Multi-Step Equations using the Hands-On Equations System - Hendrickson, Thomas C.; Horn, Annemarie (Journal of the American Academy of Special Education Professionals, 2021)
This study utilized a one-group pretest-post-posttest design (Allen, 2017) to examine the effects of the Hands-On Equations system on students’ abilities to solve multi-step equation problems following explicit classroom instruction on the skill. Participants consisted of four middle-school male students, all of whom received special education services and were educated in an inclusive general education 8th grade math class. Disability diagnoses included learning disability (LD), other health impairment (OHI), and autism spectrum disorder (ASD). All participants displayed task-initiation and completion difficulties, in addition to one student who displayed further behavioral difficulties. The intervention consisted of 24 small-group Hands-On Equations lessons focused on solving multi-step linear equations. A 10-item pre/posttest was used to evaluate participants’ performance. Results showed academic growth in three of the four participants following the Hands-On Equations intervention. Our findings, in addition to implications for research and practical application are discussed.